Impact of the Formality Level on the Strategic Planning Process of SMEs - Cadena Vinueza, Paulina Alexandra; Suquillo Guijarro, Edwin Javier; Verkovitch, Irina Evguenievna; Acosta Altamirano, José Sebastián (Journal of Ecohumanism, 2024)
The article identifies the barriers that hinder the implementation of strategic planning and the relationship with the level of formality in the preparation of strategic plans of SMEs in Quito. It focuses on the manufacturing sector and its different sub-sectors, including the manufacture of food products, textiles, clothing, as well as chemical, pharmaceutical, medicinal, and botanical substances for pharmaceutical use, in addition to rubber and plastic products. The existing literature reviewed on strategic planning and tools to address the process characterizes the small and medium-sized manufacturing sector as the object of research. The subsequent field study shows the results achieved by the companies with planning and the existence or not of barriers to strategic implementation. The most common barriers have been identified in relation to factors such as resources, culture, lack of technological support, among others. Once the barriers have been identified, they are linked to the use of planning tools to determine the type of existing relationship. There is a moderate correlation between the level of complexity and the level of execution of the strategic plan. The research results will enable further research on the importance of the use of management tools in SMEs.